Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2014
DOI: 10.1118/1.4890295
|View full text |Cite
|
Sign up to set email alerts
|

Postmortem validation of breast density using dual‐energy mammography

Abstract: The results indicate that dual energy mammography can be used to accurately measure breast density. The variability in breast density estimation using dual energy mammography was lower than reader assessment rankings, standard histogram thresholding, and fuzzy C-mean algorithm. Improved quantification of breast density is expected to further enhance its utility as a risk factor for breast cancer.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
21
0
3

Year Published

2015
2015
2023
2023

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 14 publications
(25 citation statements)
references
References 78 publications
1
21
0
3
Order By: Relevance
“…The energy information basically addresses the limitations related to the uncertainty associated with segmentation of fibroglandular tissue purely based on image gray level. Previous phantom and postmortem breast studies have validated the accuracy of breast density measurement using dual energy and spectral mammography (28, 29, 34, 38). The results from dual-energy material decomposition measurements from right and left breasts in this study also showed that volume and breast density measurements were highly correlated.…”
Section: Discussionmentioning
confidence: 98%
See 3 more Smart Citations
“…The energy information basically addresses the limitations related to the uncertainty associated with segmentation of fibroglandular tissue purely based on image gray level. Previous phantom and postmortem breast studies have validated the accuracy of breast density measurement using dual energy and spectral mammography (28, 29, 34, 38). The results from dual-energy material decomposition measurements from right and left breasts in this study also showed that volume and breast density measurements were highly correlated.…”
Section: Discussionmentioning
confidence: 98%
“…A previously reported phantom study using spectral mammography has shown that accurate volumetric breast density measurements can be made using just a single exposure (34). Previous studies have also validated the accuracy of the dual energy mammography technique for breast density measurement using chemical analysis in postmortem breasts as the reference gold standard (29, 35). The postmortem breast studies have also shown excellent correlation of breast density between right and left breasts (29, 35).…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Results based on computer simulation model, phantom and post-mortem breast studies seem promising; 26,27 although robustness and clinical utility have not been fully investigated.…”
mentioning
confidence: 99%